Trauma Transfers and Definitive Imaging: Patient Benefit but at What Cost?. Issue 3 (March 2013) - Quick, Jacob A.; Bartels, Ashley N.; Coughenour, Jeffrey P.; Barnes, Stephen L.
Many patients undergo computed tomography (CT) scan before transfer to definitive care. Despite this, studies are often repeated on arrival to the trauma center. We evaluated a policy to provide formal in-house interpretation of images performed at outside hospitals. A 3-month retrospective analysis was performed. Two groups were compared. Patients in the in-house interpretation (IHI) group underwent in-house interpretation of outside images. Those images not meeting criteria were placed in the comparison group without in-house radiologic interpretation. Demographics, CT scan data, billing and productivity loss, and extrapolated cancer risk reduction were analyzed. There were no significant differences in demographic or injury data. Fewer total CT scans were performed in the IHI group (223 vs 320, P = 0.04). The IHI group underwent fewer repeated CT scans (25 vs 62, P = 0.02; odds ratio [OR], 0.53). Fewer patients were exposed to repeat CT scans (17 vs 32; OR, 0.48). Total hospital billings decreased by $188, 285 ($4, 592/patient) in the IHI group. Uncaptured work relative value units totaled 152.19 (3.71/patient) in the IHI group. Radiation exposure decreased by 8 per cent. Use of outside hospital imaging as the definitive evaluation of injured patients is safe and results in an overall decrease in radiation exposure and healthcare cost.